Computation of nielsen and reidemeister coincidence numbers for multiple maps - Monis, Thaís Fernanda Mendes [UNESP]; Wong, Peter (Uniwersytet Mikolaja Kopernika/Nicolaus Copernicus University, 2020)
Let f1, …, fk: M → N be maps between closed manifolds, N(f1, …, fk ) and R(f1, …, fk ) be the Nielsen and the Reideimeister coincidence numbers, respectively. In this note, we relate R(f1, …, fk ) with R(f1, f2 ), …, R(f1, fk ). When N is a torus or a nilmanifold, we compute R(f1, …, fk ) which, in these cases, is equal to N(f1, …, fk ).
Keywords: Nielsen coincidence number; Nilmanifolds; Topological coincidence theory